2020
DOI: 10.14710/jnc.v9i1.26424
|View full text |Cite
|
Sign up to set email alerts
|

Konsumsi Gizi Pada Penyandang Diabetes Mellitus Di Masyarakat

Abstract: Latar belakang: Pasien dengan diabetes harus memperhatikan manajemen gizi yang sangat penting untuk mengontrol status glikemik. Salah satu fokus pengelolaan gizi pada DM adalah untuk mencegah hiperglikemia yang mungkin terjadi. Setiap individu seharusnya mengikuti ketentuan diet yang berlaku. Namun, banyak masalah gizi muncul yang mencakup pengetahuan, kesadaran, kepatuhan, dan juga implementasinya. Dengan demikian, pemantauan gizi yang dikonsumsi oleh pasien dengan DM sangat penting untuk mempertahankan hasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Small amounts of glucose that enter the body are immediately metabolized or stored as insulin while waiting for the next meal. 17 Individuals who consume a high-fat diet without regard to low physical activity could affect the energy balance by storing excess fat in the body and resulting in insulin resistance. In addition to maintaining a high-fat diet, type 2 DM patients could also reduce their consumption of a high-carbohydrate diet to lose weight and lower their FBG levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of glucose that enter the body are immediately metabolized or stored as insulin while waiting for the next meal. 17 Individuals who consume a high-fat diet without regard to low physical activity could affect the energy balance by storing excess fat in the body and resulting in insulin resistance. In addition to maintaining a high-fat diet, type 2 DM patients could also reduce their consumption of a high-carbohydrate diet to lose weight and lower their FBG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, untreated hypoglycemia could cause loss of consciousness. 17 One of Indonesia's most used meal timing schedules was the time-restricted eating model of intermittent fasting, which means individuals limit their eating schedule to a certain period. This fasting model could help patients lose weight, lower blood pressure, lipids, blood glucose, and improve insulin sensitivity by replacing glucose used in fatty acids and ketone bodies as a source of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Penyakit diabetes melitus jika dibiarkan dapat menyebabkan komplikasi kronis dan terjadi secara menahun (IDF, 2019). (1) Penyakit ini disebabkan karena pankreas yang tidak dapat berproduksi sama sekali atau hanya menghasilkan sedikit insulin sehingga tubuh kekurangan insulin dan menyebabkan kadar gula meningkat. Kepatuhan dalam menyeimbangkan pola makan, istirahat tidur, bekerja, dan olahraga merupakan perilaku hidup sehat yang harus ditaati pasien DM agar kadar gula darah tidak tinggi.…”
Section: Pendahuluanunclassified
“…Penelitian kualitatif merupakan suatu metode penelitian yang berlandaskan pada filsafat post positivisme yang menekankan pada suatu pemahaman mengenai masalah-masalah dalam kehidupan sosial berdasarkan kondisi realitas atau natural setting yang holistik, kompleks dan juga rinci. Peneliti biasanya menggunkan pendekatan naturalistik untuk memahami suatu fenomena tertentu (Anggraeni, 2017). ( 4)…”
Section: Metodeunclassified
“…The specific programs that are applied are reported to be less effective in reducing the glycated hemoglobin levels of diabetes patients (Rosdiana et al, 2017 ). Moreover, several studies have shown various problems regarding dietary adherence, physical activity, and control of blood glucose in diabetic patients (Chairani & Dk, 2018 ; Giajati & Kusumaningrum, 2020 ; Rachmawati & Kusumaningrum, 2017 ). These problems occur not only in Indonesia but also worldwide (Crichton et al, 2013 ; Iversen et al, 2015 ; Knight et al, 2016 ; Ram et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%